Exploring Lesbian and Bisexual Catholic Women's Narratives of Religious and Sexual Identity Formation and Integration. Issue 1 (2nd January 2021) - Houghton, Marie; Tasker, Fiona
ABSTRACT: Many LGBT people with a Christian upbringing experience conflict between their religious and sexual identities. Many resolve this conflict by leaving Christianity, others by moving to affirming churches. Some research has examined the experiences of LGBT people who choose to attend conservative churches; however, there has been very little research on the experiences of non-heterosexual women in the Catholic Church. Narrative and thematic analyses of data collected through qualitative interviews with six non-heterosexual Catholic women revealed several ways participants had integrated their faith and sexuality: acceptance from other Catholics, distinguishing between the Church and God, meeting other LGBT Christians, and developing a personal relationship with God. These reflect strategies adopted by gay Catholic men and LGBT Christians attending Protestant churches. Nonetheless, participants reported that their experiences varied from those of gay Catholic men due to gay men being more visible and more subject to prejudice within the Church.